1999
DOI: 10.1039/a809547g
|View full text |Cite
|
Sign up to set email alerts
|

Resonance enhanced multiphoton ionisation probing of H atoms in a hot filament chemical vapour deposition reactor

Abstract: We demonstrate some of the merits and limitations of using multiphoton ionisation (MPI) spectroscopy, resonance enhanced at the two photon energy by the state, to detect H atoms within a hot Ðlament 2s1 ;2S 1@2 reactor used for diamond chemical vapour deposition (CVD). Subsequent analysis of the Doppler broadened lineshapes obtained in this way allows determination of spatially resolved, relative H atom number densities and gas temperatures. The e †ects of pressure and Ñow rate, Ðlament temperature and radial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
36
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 55 publications
5
36
0
Order By: Relevance
“…(If the chamber were coated with amorphous silicon from other studies, SiH 4 would be etched from surfaces by H, perhaps producing such an anomalous p dependence.) Similar values of E diss have also been observed for H 2 dissociation on other metals [17]. The striking fact that 2E diss ffi E H 2 , the vapor-phase H 2 dissociation energy, for all metals studied has long been recognized.…”
Section: Introductionsupporting
confidence: 53%
“…(If the chamber were coated with amorphous silicon from other studies, SiH 4 would be etched from surfaces by H, perhaps producing such an anomalous p dependence.) Similar values of E diss have also been observed for H 2 dissociation on other metals [17]. The striking fact that 2E diss ffi E H 2 , the vapor-phase H 2 dissociation energy, for all metals studied has long been recognized.…”
Section: Introductionsupporting
confidence: 53%
“…34 The most common filament materials are W, Ta, or Re because of their high melting points. Laser and mass spectroscopic measurements of key species (including H atoms, [35][36][37][38][39][40] and CH3 radicals 37,41,42 ) in HF-activated CH4/H2 gas mixtures, coupled with thermodynamic and gas-kinetic modelling, 27,43 have yielded a fairly complete picture of the prevailing gas-phase chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…In this technique, radical species are produced from material gases on heated metal surfaces without co-producing ionic or metastable excited species. In order to make clear the decomposition and ejection mechanisms, many studies have been carried out to identify the radical species produced [3][4][5][6][7][8][9][10][11][12][13][14][15][16]. Although it has been rather difficult to produce oxidizing radicals, we have recently shown that atomic oxygen can be produced efficiently by the catalytic decomposition of O 2 , NO, N 2 O, and NO 2 on a heated Ir filament [7,8].…”
Section: Introductionmentioning
confidence: 99%